Immunopathogenesis of psoriasis: a possible role of TGFβ/Smads pathway - Sferra, Roberta; Fargnoli, Maria Concetta; Corbelli, Eleonora; Pellegrini, Cristina; Peris, Ketty; Gaudio, Eugenio; Vetuschi, Antonella (Italian Journal of Anatomy and Embryology, 2015)
Psoriasis is a chronic immune-mediated inflammatory skin disease with both genetic and environmental factors contributing to its pathogenesis. Transforming Growth Factor beta (TGFβ) is a member of a large family of pleiotropic cytokines with three different isoforms (TGFβ1,2,3). Smads are a family of eight-related proteins that function as intracellular signaling intermediates for TGFβ once the latter is bound to its receptors (TGFbRI, II and III). The involvement of Smads in TGFβ signaling has been studied intensively in the skin in the process of wound healing. Few studies, and with controversial results, have investigated at the immunohistochemical and molecular level the role of TGFβ/Smads signaling in psoriasis.